Contemporary development of Hunan calligraphy education: Qing dynasty to modern education - Gao, Feng; Khiatthong, Thongchue (Edelweiss Applied Science and Technology, 2024)
Calligraphy is a major subject in contemporary art in Hunan Province. Therefore, historical and cultural expressions through the evaluation system of society and schools are necessary in all eras. This paper thus presents a contemporary development of the study of Hunan calligraphy, the Qing Dynasty, for modern education. The purpose of this study was to: (1) study and analyze the characteristics of calligraphy styles in Hunan Province during the Qing Dynasty. (2) To analyze the current development status of calligraphy education at the Contemporary Hunan University. (3) Evaluate the model and formulate a development strategy for a new form of professional calligraphy education in contemporary universities. This study used a mixed-method design consisting of quantitative and qualitative research. Different research tools were used to study and analyze the data on three issues: first, representatives of calligraphers from the Qing Dynasty, and related works. The second issue is current developments and modeling. A survey was conducted using questionnaires and expert interviews about the current state of development of calligraphy professional education in universities in Hunan. Third issue: Define a model development strategy. However, the results of a variety of data analyses with reliability and accuracy can analyze six main factors with descriptive analysis, demonstrating the effectiveness of each dimension. Correlation and regression analyses have proven the five factors of the curriculum system, faculty, learning resources, student development, and professional management. This had a significant positive impact on the contemporary development of Hunan calligraphy education: the Qing Dynasty for modern education. The results of these analyses show that the calligraphy education model in Hunan during the Qing Dynasty was effectively inherited and developed.